Perceptions of healthy aging among Francophone older adults living in Edmonton, Alberta [master's thesis, University of Alberta] - Esso, Christelle. M.-C. (University of Alberta, 2013)
fs-ref-orig: Esso, C. M.-C. (2013). Perceptions of healthy aging among Francophone older adults living in Edmonton, Alberta [master's thesis, University of Alberta]. Education & Research Archive. https://doi.org/10.7939/R3R785X66 fs-code-orig: Esso-2013

Enjeux du vieillissement chez les Africains en milieu francophone minoritaire canadien - Mulatris, Paulin; Bahi, Boniface (Alterstice, 2014)
Les enjeux du vieillissement des populations francophones d’origine africaine subsaharienne sont très peu connus. Une analyse de données qualitatives portant sur le vécu socioculturel et les déterminants de la santé, obtenues au moyen d’entrevues semi-structurées auprès d’immigrants francophones africains subsahariens des régions urbaines d’Edmonton et Calgary, permet de constater que cette population cumule des défis culturels et économiques qui les poussent à développer un mode de vie inapproprié aux conditions d’un vieillissement en santé. La nécessité que ces Néo-Canadiens développent des habitudes de vie adaptées mène à une réflexion sur les conditions socioéconomiques auxquelles ils font face et sur l’adaptation culturelle des soins.

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.